Strategic Technology Partnering and Supply Chain Risk Management Five Selected Essays - Kilubi, Irène (Supply Chain Management, Beiträge zu Beschaffung und Logistik,, 2018)
With her work, Irène Kilubi builds a bridge between two areas of business research, on the one hand the supply chain management, and on the other hand innovation and technology management. In the context of her work, she proposes to expand the usual instruments of supply chain risk management by strategic technology partnerships, which not only provide procurement alternatives but also the possibility to develop technological alternatives at short notice. More precisely, she advocates that the capabilities needed for STP serve as enablers for effective SCRM. Accordingly, connections between supply chain risk management and strategic technology partnering are presented and a conceptual framework is correspondingly created. Contents Investigating current paradigms in Supply Chain Risk Management 26 years of Strategic Technology Partnering The strategies of Supply Chain Risk Management Bridging the gap between Supply Chain Risk Management and Strategic Technology Partnering - Insights from two theoretical lenses Target Groups Students and lecturers in business administration, industrial engineering and management (notably supply chain management, innovation and technology management, risk management) Practitioners in corporate supply chain management, corporate development, corporate finance (risk management), corporate technology. The Author Irène Kilubi (PhD, MSc) is a Senior Procurement Consultant at an inhouse consultancy within the corporate development center.